2022
DOI: 10.3390/cells11142251
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Fibroblast Growth Factor 21 Levels Decrease during Early Pregnancy in Normotensive Pregnant Women but Are Higher in Preeclamptic Women—A Longitudinal Study

Abstract: (1) Background: Fibroblast growth factor 21 (FGF-21) is an endocrine factor involved in glucose and lipid metabolism that exerts pleiotropic effects. The aim of this study was to investigate the serum FGF-21 profile in healthy and mild preeclamptic pregnant women at each trimester of pregnancy; (2) Methods: Serum FGF-21 levels were determined by ELISA in a nested case-control study within a longitudinal cohort study that included healthy (n = 54) and mild preeclamptic (n = 20) pregnant women, women at three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
2
2
Order By: Relevance
“…This study has demonstrated for the first time that FGF21 is not divergent between prepubertal and postpubertal heifers nor across the phases of the estrous cycle of beef heifers. Our finding that the circulating concentration of FGF21 is not correlated with the circulating concentration of progesterone in beef heifers contradicts the findings of others [20] that observed a negative correlation between circulating FGF21 and progesterone in women. Another report [21] also supports these findings [20] indirectly by presenting that the activation of the hepatic estrogen receptor-α increases energy expenditure by stimulating the production of FGF21 in mice.…”
Section: Heifer Reproductive Statuscontrasting
confidence: 89%
See 1 more Smart Citation
“…This study has demonstrated for the first time that FGF21 is not divergent between prepubertal and postpubertal heifers nor across the phases of the estrous cycle of beef heifers. Our finding that the circulating concentration of FGF21 is not correlated with the circulating concentration of progesterone in beef heifers contradicts the findings of others [20] that observed a negative correlation between circulating FGF21 and progesterone in women. Another report [21] also supports these findings [20] indirectly by presenting that the activation of the hepatic estrogen receptor-α increases energy expenditure by stimulating the production of FGF21 in mice.…”
Section: Heifer Reproductive Statuscontrasting
confidence: 89%
“…Our finding that the circulating concentration of FGF21 is not correlated with the circulating concentration of progesterone in beef heifers contradicts the findings of others [20] that observed a negative correlation between circulating FGF21 and progesterone in women. Another report [21] also supports these findings [20] indirectly by presenting that the activation of the hepatic estrogen receptor-α increases energy expenditure by stimulating the production of FGF21 in mice. The differences in findings between the aforementioned and current report are potentially attributed to differences in species, divergent regulatory mechanisms of action, or differences in lag time to observable change in circulatory FGF21 between models.…”
Section: Heifer Reproductive Statuscontrasting
confidence: 89%
“…Previous cross‐sectional investigations have shown a substantial rise in maternal FGF‐21 levels in women with preeclampsia in comparison to pregnant women who do not have hypertension 25 . Longitudinal cohort research has shown that serum FGF‐21 levels are markedly elevated in pregnant women with preeclampsia as compared to healthy pregnant women with normal blood pressure during all three trimesters of pregnancy 26 . FGF21 level was shown to be a risk factor for PE in research employing binary logistic regression analysis 27 .…”
Section: Discussionmentioning
confidence: 98%
“… 25 Longitudinal cohort research has shown that serum FGF‐21 levels are markedly elevated in pregnant women with preeclampsia as compared to healthy pregnant women with normal blood pressure during all three trimesters of pregnancy. 26 FGF21 level was shown to be a risk factor for PE in research employing binary logistic regression analysis. 27 In a community sample, FGF21 was shown to be independently related to hypertension.…”
Section: Discussionmentioning
confidence: 99%